2021
DOI: 10.1002/col.22641
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception of natural colours in paintings: An eye‐tracking study of Grünewald's Resurrection

Abstract: This article aims to reveal aspects of the visual perception of the natural colours of Matthias Grünewald's Resurrection panel, part of the Isenheim Altarpiece (1512‐1516). To identify, which colours are mostly perceived, we have performed an eye‐tracking study with 52 participants at the Unterlinden Museum, in Colmar, France, in which we recorded the participant's eye movements and their spontaneous comments when looking at Grünewald's work, using an innovative approach to let visitors be free while recording… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Most museums still maintain the traditional form of object orientation, displaying exhibits in cabinets with basic labels and then ending the educational mission [1,2]. Although countless "high level" "fine art" collections are on display, the value of the collections is hardly understood, and for most visitors, it is just a visit to the museum.…”
Section: Introductionmentioning
confidence: 99%
“…Most museums still maintain the traditional form of object orientation, displaying exhibits in cabinets with basic labels and then ending the educational mission [1,2]. Although countless "high level" "fine art" collections are on display, the value of the collections is hardly understood, and for most visitors, it is just a visit to the museum.…”
Section: Introductionmentioning
confidence: 99%
“…A colleague raised questions about the same pigments: Volkon's Green Earth and Gutankara's Purple; they were unable to identify them precisely. The authors of the article suggested that Tübke used these pigments to imitate the paintings of the old masters [36,37]. This theory is currently being refined; we plan to report on it in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The think-aloud method revealed that the participants admired the real Night Watch more than the replica. This effect may have been caused by the painting itself but also by the context of the museum ( Brieber et al, 2014 ; Krukar & Dalton, 2020 ; Specker et al, 2017 ; see Pelowski et al, 2017 , for a review of the factors that determine people's experience of art in a museum). Although the participants’ level of admiration was substantially different between the real painting and the replica painting, the heatmaps were very similar ( r = 0.95, or r = 0.99 when considering only the first minute of viewing).…”
Section: Discussionmentioning
confidence: 99%
“…Using eye-tracking software ( Kassner et al, 2014 ), the video footage of the mobile eye-tracker was mapped to a frontal image of the painting. The study by Walker et al was conducted on five paintings, the smallest having a length × width of 46 × 39 cm and the largest 101 × 50 cm, viewed from a relatively large distance of 3 m. More recently, Fontoura and Menu (2021) created a heatmap for a 141 × 269 cm painting viewed by visitors of the Unterlinden Museum in France. They used the eye-tracker developer's Real-World Mapping algorithm to map gaze data to snapshots of the painting without using markers.…”
mentioning
confidence: 99%